2008
DOI: 10.1002/bit.21882
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid: A viable alternative to sodium butyrate for enhancing protein expression in mammalian cell cultures

Abstract: Various DNA methyl transferase inhibitors (iDNMTs) and histone deacetylase inhibitors (iHDACs) were screened for their ability to enhance transient gene expression (TGE) in Human Embryonic Kidney 293-EBNA (HEK293E) cells. The effects in HEK293E cells were compared to those in Chinese Hamster Ovary DG44 (CHO-DG44) cells. The iDNMTs and iHDACs were chosen based on their different cellular activities and mechanisms of action. For each inhibitor tested, the optimum concentration was determined for both cell lines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 32 publications
(34 reference statements)
3
113
1
4
Order By: Relevance
“…Furthermore, we found that Steap3 expression was enhanced when valproic acid was added to the transfection medium. Valproic acid is a histone deacetylase inhibitor that has been shown previously to enhance transient gene expression in HEK-293 cells (14). The presence of valproic acid in the 293F transfection medium resulted in a ϳ1.6-fold increase in expression of Steap3-Venus over unsupplemented expression.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, we found that Steap3 expression was enhanced when valproic acid was added to the transfection medium. Valproic acid is a histone deacetylase inhibitor that has been shown previously to enhance transient gene expression in HEK-293 cells (14). The presence of valproic acid in the 293F transfection medium resulted in a ϳ1.6-fold increase in expression of Steap3-Venus over unsupplemented expression.…”
Section: Resultsmentioning
confidence: 95%
“…Total RNA Extraction and RT-PCRs-Total RNA samples obtained from seven tissues (testis, brain, liver, spleen, kidney, skeletal muscle, and ovary) of adult mouse, cDNA from germ cell-devoid testes of W/W v mutant mice, and prepubertal and adult male mice (aged 8,10,12,14,16,20,30, and 84 days) were used for reverse transcription. Total RNA was extracted using TRIzol TM Reagent (MRC) according to the manufacturer's protocol, and cDNA was synthesized by random hexamer and oligo(dT) priming with Omniscript reverse transcriptase (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Protein Samples and Western Blot Analysis-Western blot analysis was performed using protein samples from the testes of prepubertal and adult male mice (aged 8,10,12,14,16,20,30, and 84 days) as well as germ cell-devoid testes of W/W v mutant mice. Testicular cells and sperm from testes of normal adult male mice were isolated by suspension in 52% isotonic Percoll (GE Healthcare) and centrifugation for 10 min (27,000 ϫ g, 10°C) and were resuspended in Mg 2ϩ -Hepes buffer (7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations